1999
DOI: 10.1038/6338
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NMDA receptors reverses desensitization of mGluR5 in native and recombinant systems

Abstract: The metabotropic glutamate receptor, mGluR5, has a critical role in induction of NMDA-receptor-dependent forms of synaptic plasticity and excitotoxicity. This is likely mediated by a reciprocal positive-feedback interaction between these two glutamate receptor subtypes in which activation of mGluR5 potentiates NMDA receptor currents and NMDA receptor activation potentiates mGluR5-mediated responses. We have investigated the mechanism by which NMDA receptor activation modulates mGluR5 function and find evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
131
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(143 citation statements)
references
References 39 publications
11
131
0
Order By: Relevance
“…Previous studies have shown that NMDA potentiates mGluR5 responses (Challiss et al, 1994;Luthi et al, 1994). We have previously shown that a likely mechanism for this effect is via reversal of PKC-mediated desensitization of mGluR5 (Alagarsamy et al, 1999a). Our previous report and current data are consistent with the hypothesis that NMDA activates PP2B/calcineurin to mediate reversal of mGluR5 desensitization and that calcineurin acts by interaction with, and dephosphorylation of, the C-terminus of mGluR5.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Previous studies have shown that NMDA potentiates mGluR5 responses (Challiss et al, 1994;Luthi et al, 1994). We have previously shown that a likely mechanism for this effect is via reversal of PKC-mediated desensitization of mGluR5 (Alagarsamy et al, 1999a). Our previous report and current data are consistent with the hypothesis that NMDA activates PP2B/calcineurin to mediate reversal of mGluR5 desensitization and that calcineurin acts by interaction with, and dephosphorylation of, the C-terminus of mGluR5.…”
Section: Discussionsupporting
confidence: 90%
“…Xenopus oocytes were injected and recorded from as previously described (Alagarsamy et al, 1999a). Briefly, oocytes were injected with in vitro transcribed mRNA encoding mGluR5a alone or in the presence of mRNA for a constitutively active mutant form of calcineurin (CaNa) (Friday et al, 2000).…”
Section: Xenopus Oocyte Recordingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, NMDARs have been reported to stimulate mGluRs, and vice versa (Aniksztejn et al, 1992;Harvey and Collingridge, 1993;Challiss et al, 1994;Lüthi et al, 1994;Fitzjohn et al, 1996;Gereau and Heinemann, 1998;Alagarsamy et al, 1999;Collett and Collingridge, 2004). This feedback loop between mGluR and NMDARs may be important in regulating both NMDAR-dependent and mGluR-dependent forms of synaptic plasticity and could contribute to pathological responses induced by NMDA receptor activation.…”
Section: Inhibition Of Glun2b Suppresses Ltdmentioning
confidence: 99%